The Role of Parenting and Family Factors in the Developmental Catch-Up for Children Adopted Internationally. Issue 3 (2nd July 2016) - Katzenstein, Jennifer M.; LeJeune, Brenna C.; Johnson, Kathy E.
ABSTRACT: Internationally adopted children are at greater risk for cognitive difficulties. While age at adoption is an established significant predictor of cognitive outcomes, considerable variation persists. The present study focused on whether parenting and family factors explain additional variance in cognitive and linguistic catch-up in this group of children. In total, 46 children were examined at two time points, approximately 12 months apart. Cognitive and linguistic abilities were measured at both time points, with parenting and family factors examined at follow-up, using hierarchical linear regression. Age at adoption and baseline cognitive abilities were the best predictors of cognitive and linguistic catch-up; parenting and family factors generally did not account for a significant increase in explained variance.